RESEARCH ON THE DEVELOPMENT OF THE "ONE-STOP" ELDERLY CARE SERVICE CASE STUDY OF THAILAND - Sun, Fangmiao; Bi, Chuanchen (International Journal of Engineering Technologies and Management Research, 2022)
The pace of population aging in China is accelerating. According to the data from World Population Prospects, issued by the United Nations, the proportion of China's aging population with the age over 65 will double from 2010 to 2030, and the aging population will account for more than one fourth of the total population in 2050. The population aging will not only bring challenges to the elderly care, but also influence the economy, as well as various aspects of the society. The new mode of the "one-stop" elderly care service promotes the effective matching between the supply and demand of elderly care service from three major sectors of intelligent equipment, online platform and software, and offline service system. This paper mainly deeply analyzes related policies of the elderly care service, relevant academic papers and conference materials issued by domestic and foreign experts and scholars, in combination with Thailand's environment, medical care, services, consumption, etc. to have a detailed introduction to Thailand's elderly care service. Similar to China, Thailand is also a developing country and shares a great similarity with China. In the meanwhile, China is also a populous country. The study of Thailand's elderly care service can provide some suggestions and choices for China's retired groups.